Continuous glucose monitoring: A review of the evidence in type 1 and 2 diabetes mellitus - Lin, Rose; Brown, Fran; James, Steven; Jones, Jessica; Ekinci, Elif (Diabetic medicine, 2021)
Context and Aim Continuous glucose monitoring (CGM) is becoming widely accepted as an adjunct to diabetes management. Compared to standard care, CGM can provide detailed information about glycaemic variability in an internationally standardised ambulatory glucose profile, enabling more informed user and clinician decision making. We aimed to review the evidence, user experience and cost‐effectiveness of CGM. Methods A literature search was conducted by combining subject headings ‘CGM’ and ‘flash glucose monitoring’, with key words ‘type 1 diabetes’ and ‘type 2 diabetes’, limited to ‘1999 to current’. Further evidence was obtained from relevant references of retrieved articles. Results There is a strong evidence for CGM use in people with type 1 diabetes, with benefits of reduced glycated haemoglobin and hypoglycaemia, and increased time in range. While the evidence for CGM use in type 2 diabetes is less robust, similar benefits have been demonstrated. CGM can improve diabetes‐related satisfaction in people with diabetes (PWD) and parents of children with diabetes, as well as the clinician experience. However, CGM does have limitations including cost, accuracy and perceived inconvenience. Cost‐effectiveness analyses have indicated that CGM is a cost‐effective adjunct to type 1 diabetes management that is associated with reduced diabetes‐related complications and hospitalisation. Conclusions Continuous glucose monitoring is revolutionising diabetes management. It is a cost‐effective adjunct to diabetes management that has the potential to improve glycaemic outcomes and quality of life in PWD, especially type 1 diabetes.